Analysis Of Technological, Pedagogical, And Content Knowledge (TPACK) Competencies Of Madrasah Ibtidaiyah (PGMI) Teacher Education Students As A 21st Century Learning Framework - Badruzzaman, Achmad; Ulfa, Saida; Oktaviani, Herlina Ike (Universitas Negeri Malang, 2024)
Technology plays an important role as a tool, process, and resource for learning and implementing learning. The use of technology apart from offering various opportunities for better and more interesting learning experiences, also poses big challenges. Religion-based educational institutions, in this case madrasas, are required to be able to adapt to modern scientific discourse. TPACK, which is a knowledge framework, exists to explain the three main components of teacher knowledge (content, pedagogy, and technology). This research aims to describe the TPACK competencies of madrasah ibtidaiyah teacher education students. The method used is descriptive quantitative research method. Data was obtained from students of the Madrasah Ibtidaiyah Teacher Education Study Program (PGMI) Ma'had Aly Al-Hikam Islamic College (STAI) Malang Academic Year 2023/2024 who had implemented the School Field Introduction (PLP) program. The results of the research show that the competency of madrasah ibtidaiyah teacher education students is in the good category with details Technological Knowledge (TK), Content Knowledge (CK) and Pedagogical Content Knowledge (PCK) is categorized as high value while aspect Pedagogical Knowledge (PK), Technological Content Knowledge (TCK), Technological Pedagogical Knowledge (TPK), and Technological Pedagogical Content Knowledge (TPACK) is categorized as medium value. Keywords: 21st Century; TPACK; Madrasah Ibtidaiyah Teacher Education Students